2018
DOI: 10.5944/educxx1.19559
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of Auto-Scored Online Exams in Blended Assessment: Feedback for Improvement

Abstract: Cómo referenciar este artículo/how to reference this article:Riera, J.; Ardid, M.; Gómez-Tejedor, J.A.; Vidaurre, A. & Meseguer-Dueñas, J.M. (2018). Students' perception of auto-scored online exams in blended assessment: feedback for improvement. Educación XX1, 21(2), 79-103, doi: 10.5944/educXX1.19559 Riera, J.; Ardid, M.; Gómez-Tejedor, J.A.; Vidaurre, A. & Meseguer-Dueñas, J.M. (2018). Percepción de los estudiantes acerca de los exámenes online con corrección automática en una evaluación mixta: retroalim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…In another context, researches showed that the teacher's availability during the examination period is important for the students, in case the student faced confusion, particularly with automated grading forms. In turn, this may affect students' attitudes and perceptions toward online education (13) .…”
Section: Discussionmentioning
confidence: 99%
“…In another context, researches showed that the teacher's availability during the examination period is important for the students, in case the student faced confusion, particularly with automated grading forms. In turn, this may affect students' attitudes and perceptions toward online education (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Referral sampling technique have been used to collect the data from respondent (Riera et al, 2018). The respondents were university students from Malaysia and Pakistan.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of student acceptance studies that have appeared with respect to online assessment have focused on its use in medical and/or health education (Bloom et al, 2018;Boevé et al, 2015;Deutsch et al, 2012;Jawaid et al, 2014;Lewis & Sewell, 2007;Usir & Ahamad, 2017;Wadley et al, 2014), with a smaller number examining its use in subject areas such as engineering (Riera Guasp et al, 2018), foreign language studies (Fageeh, 2015) and social science education (Hewson & Charlton, 2019). This section presents a brief review of studies that have appeared internationally across these discipline areas.…”
Section: Students' Acceptance Of Online Assessmentmentioning
confidence: 99%
“…It is clear from this review that while the majority of studies conducted thus far have suggested an overall positive response from students toward online assessment, findings from others have been more mixed. Such mixed responses accumulated from system usage problems faced by students as well as the negative and indifferent attitudes towards online assessment system, and the automatic scoring process within (Boevé et al, 2015;Jawaid et al, 2014;Riera Guasp et al, 2018). While the level of detail provided in these papers did not allow for the identification of the critical factors that moderated students' responses, it is likely that the specific characteristics of the online assessment approaches or systems used in each study contributed to this variability.…”
Section: Cirit (mentioning
confidence: 99%